Characteristics Of Small-Scale Enterprises In West Sumatra - Syarif, Syahrial (Asian Academy of Management (AAM), 2004)
Small-scale enterprises in West Sumatra experienced slow growth and some constraints in their development process. In 1998, small businesses represented 99.61% of total business units operating in West Sumatra and absorbed 88.8% of total employment. The orientation of their businesses mostly on domestic market although recently they enter international market. Export contribution of small businesses still very low but growing steadily during the last three years. This research showed that enterprises dealing with embroideries, garments and handicrafts are ambitiously orienting their products towards foreign markets. At the same time these business categories are also proven to be the most profitable businesses.